Probabilistic simulation framework for balanced and unbalanced low voltage networks. (November 2016) - Klonari, Vasiliki; Toubeau, Jean-François; De Grève, Zacharie; Durieux, Olgan; Lobry, Jacques; Vallée, François
Highlights: A probabilistic tool for long term LV network observability studies is presented. Both balanced and unbalanced network configurations can be simulated. The PDFs of network state random variables are based on real smart meters datasets. Most LV network's operation indices are evaluated with offline state estimation. A real grid with unbalanced loads and mutual coupling between phases is simulated. Abstract: In Low Voltage (LV) distribution networks, the high volatility of distributed photovoltaic (PV) generation has a severe impact on the variation of operation indices, in steady state conditions. During periods with high PV injection and low demand, LV feeders are more and more subject to overvoltage events and temporary PV units' cut-offs. As a result, the delivered power quality is affected and network operational expenses increase. Moreover, the income of the PV owner is decreased due to the loss of generated energy. For efficiently addressing such operational issues, long term observability analytics of the LV network are required. Distribution System Operators (DSOs) currently deploy such studies in a deterministic manner, focusing on "worst-case" hypothesis, without considering the uncertainty of nodal power injection and consumption. This approach can lead to over restrictive decisions and costly technical solutions. For refining DSO strategies to the variability of network states, probabilistic methods are highly recommended. In this context, this paper presents a Monte-Carlo (MC) framework that simulates the steady operation of the LV network by elaborating user-specific smart metering (SM) measurements. The presented framework integrates a complete three-phase power flow algorithm that can analyse most possible LV network configurations, balanced and unbalanced, considering nodal power injections and consumptions as random variables of each network state. Such unbalanced power flow algorithms had not up to now been linked with probabilistic analysis using network-specific SM readings. For demonstrating the interest of the proposed framework, the latter is used to simulate several configurations in an existing LV feeder with high PV integration and SM deployment.